PENGEMBANGAN MEDIA SOCIAL SKILL CARD UNTUK MENINGKATAN KETERAMPILAN SOSIAL SISWA - RIDWAN; Supriatna, Ecep; Novianti, Wiliya (IKIP Siliwangi, 2023)
this research motivated by MA nurul iman sindangkerta school students who have low level of social skill who characterized by less of interaction with their surround environment. it leads to student feel uncomfortable to reveal their opinions and still appears are less concerned toward their surround friends. the aim of this development research conducted by researcher to understand the properness of social skill card game the social skill card is learning media in the form of a card which using to improve social skill through a group guidance. the data collection technique of this research is through pre-test and post-test by using social skill instrument. meanwhile, the subject of this research are the first grade of senior high school students from class A and class B with the number of students 40 people by filling in statement questioner of social skills. based on the result of this research , social skill card media is able to improve social skill students, it can be seen from the trial of pre-test and post-test from class A showed result 92% and class B showed result 89%. the conclusion of this research is social skill card game through group guidance can improve the social skill of the first grade senior high school students in MA Nurul Iman Sindangkerta.